Pelatihan Rekayasa Proses untuk Meningkatkan Kualitas Produk Minuman Sari Buah Kedondong dan Kukis Kelapa - Amrinola, Wiwit; Romulo, Andreas (LPkM Universitas Bakrie, 2024)
UMKM Lie Dong is engaged in the business of making kedondong juice and coconut kukis. However, the kedondong juice and kukis produced have a relatively short shelf life, meaning the product can only be sold for a short time. Therefore, efforts are needed to improve quality and quality through improving the production process and kedondong juice. This community service activity aimed to provide process training to enhance the quality of kedondong juice and coconut kukis. The community service activities were carried out through preparation stages, discussions, transfer of knowledge and technology, and direct training at the production location. The training involved several activities, such as a workshop on hot filling and pasteurization technology, using active packaging for cookie products, improving packaging design, and socialization on Good Manufacturing Practices. UMKM Lie Dong felt the results of the service activities, where the training provided increased knowledge and skills related to processing engineering, providing benefit to products where the kedondong juice and coconut kukis produced had better quality and longer shelf life.